2023
DOI: 10.3390/s23094343
|View full text |Cite
|
Sign up to set email alerts
|

Application of Air-Coupled Ground Penetrating Radar Based on F-K Filtering and BP Migration in High-Speed Railway Tunnel Detection

Abstract: As the number and length of high-speed railway tunnels increase in China, implicit defects such as insufficient lining thicknesses, voids, and poor compaction have become increasingly common, posing a serious threat to train operation safety. It is, therefore, imperative to conduct a comprehensive census of the defects within the tunnel linings. In response to this problem, this study proposes a high-speed railway tunnel detection method based on vehicle-mounted air-coupled GPR. Building on a forward simulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…To reduce this effect and consider the minimum allowable distance to the rock paintings on the Ceiling, data acquisition was performed at a height depending on the 1.6 GHz central-frequency antenna of 10 cm (Figure 5). This height ensured the maximum possible amount of energy transmitted to the rock mass and reduced the effects of coupling to the air to obtain accurate and high-quality GPR records [89,90]. This antenna configuration provided a penetration depth of up to approximately 50 cm into the Polychrome Layer, while maintaining a high-resolution capability [58,80,81].…”
Section: Gpr Data Acquisitionmentioning
confidence: 99%
“…To reduce this effect and consider the minimum allowable distance to the rock paintings on the Ceiling, data acquisition was performed at a height depending on the 1.6 GHz central-frequency antenna of 10 cm (Figure 5). This height ensured the maximum possible amount of energy transmitted to the rock mass and reduced the effects of coupling to the air to obtain accurate and high-quality GPR records [89,90]. This antenna configuration provided a penetration depth of up to approximately 50 cm into the Polychrome Layer, while maintaining a high-resolution capability [58,80,81].…”
Section: Gpr Data Acquisitionmentioning
confidence: 99%
“…Several authors have conducted software simulation studies and real measurements of the optimal height of antennas relative to a surface during data collection over the last decades [66][67][68][69][70][71][72][73]. These authors concluded that the best GPR data are obtained when antennas are in contact with the ground or close to the ground.…”
Section: Ground-penetrating Radarmentioning
confidence: 99%
“…To solve the problem of defect detection in tunnels, Zhai et al [11] proposed a dual-frequency radar signal time-domain coherence calculation to suppress interference. Lei et al [12] proposed an on-board air-coupled GPR approach for high-speed railroad tunnel detection. Svorc et al [13] utilized infrared video streaming to validate the detection and classification of vehicles.…”
Section: Introductionmentioning
confidence: 99%